Self-Adaptation Management of Thailand Students in the Teacher Training Program at Islamic Universities in Indonesia : Manajemen Adaptasi Diri Mahasiswa Thailand dalam Program Pendidikan Guru di Universitas Islam di Indonesia - Salsabilla, Imelia Sahda; Wahyudi, Wahyudi; Nasikhin, Nasikhin; Asiyah, Nur; Panaemale, Abdul Razak Abdulraya (Universitas Muhammadiyah Sidoarjo, 2025)
This research aims to understand the self-adaptation management of students from Thailand who are pursuing teacher training study programs in Indonesia. The focus of the research includes: 1) cultural differences between Thailand and Indonesia that affect students' self-adaptation, 2) the self-adaptation strategies used by Thai students, and 3) their expectations for self-adaptation management at the university. The method used was qualitative with a narrative inquiry approach through interviews and observations of 9 respondents. The results showed that Thai students at the Islamic University of Indonesia observed cultural differences in social values, norms, and religious aspects that influenced social interaction, responses to authority, and understanding of dominant cultures as well as lifestyles and perceptions of time. They develop adaptation strategies through Indonesian language courses, international communities, technology, lecturer guidance, and local friendships. Students expect the university to provide orientation programs, guidance, comfortable dormitories, cultural exchange, inclusive activities, and community support, as well as ensure the quality of higher education, competent lecturers, and relevant curriculum. This research provides insights for universities to develop more effective orientation and mentoring programs and shows the importance of technology support in the adaptation process. The limitation of this study is that its scope is limited to one university with a small number of respondents, so it is recommended for future research to include more universities and a wider range of respondents for a more comprehensive understanding. Keywords: Students, International, Environmental Adaptation, Universities, Indonesia.